A comparative analysis of sensory visual evoked oscillations with visual cognitive event related oscillations in Alzheimer's disease - Yener, Görsev G.; Güntekin, Bahar; Tülay, Elif; BAŞAR, EROL (ELSEVIER IRELAND LTD, ELSEVIER HOUSE, BROOKVALE PLAZA, EAST PARK SHANNON, CO, CLARE, 00000, IRELAND, 2009)
We compared visual evoked oscillatory responses of subjects with Alzheimer's disease (AD) (n = 22) to healthy elderly controls (n = 19) elicited by simple light stimuli. The visual evoked oscillatory responses in AD subjects without cholinergic treatment (n = 11) show significant differences (df = 2.38. F = 4.957, P = 0.012) from the controls and the AD subjects treated with a cholinesterase inhibitor (n = 11). Higher theta oscillatory responses in untreated AD subjects are seen on the electrode locations over bi-parietal and right occipital regions after simple light stimuli with less, if any, cognitive load. These changes were restricted to the theta frequency range only and are related to location, frequency bands and drug effects. In our previous work we observed that visual event related oscillations elicited after the visual stimuli with a higher cognitive load, i.e. an oddball target, display lower amplitudes: between controls and AD subjects in delta frequency band without a drug effect, over the left and mid-central region. These differences between the visual evoked oscillations and the visual event related oscillations imply that there are at least two different cognitive circuits that are activated upon visual stimuli in AD patients. (c) 2009 Published by Elsevier Ireland Ltd.
Keywords: visual evoked potential; sensory; event related potential; alzheimer; cholinergic; oscillation; theta; dementia; alpha; eeg; responses; impairment; stage; delta; görsel uyarılmış potansiyel; duyusal; olaya ilişkin potansiyel; kolinerjik; salınım; teta; bunaklık; alfa; tepkiler; bozulma; sahne; delta